Asean School Games Tennis Referee Anxiety - Rices Jatra; Rezki Rezki (JUARA : Jurnal Olahraga, 2022)
Leading the match is not easy. Nowadays, there are many obstacles when leading the competition, starting from the regional to the international level. There are errors that sometimes we can't immediately conclude what the cause is. One of the causes of mistakes in leading the match is anxiety, whereby having a solid level of anxiety. There can be fear in deciding something, especially the large number of spectators, coaches, Referees who always watch the match and other officials, and internal factors that are said to be from within or extrinsic. This study aims to see the anxiety of tennis referees on duty at the Asean Schools Games in the field tennis branch. This research is a quantitative descriptive study conducted at the Tri Competition Juang Tennis Court in Semarang in September 2019. The data was collected using the anxiety questionnaire method. Population The total number of referees on duty in the Asean Schools Games in the Tennis Court is 16 people. The sampling technique used was total sampling. The data that has been collected from the results of the research test get the following results: (1) the level of anxiety of the tennis referee when leading the Asian school games is in the moderate category, (2) the intrinsic factors that affect anxiety are in the "moderate" category, and (3 ) extrinsic factors that also influence the anxiety that arises in a referee are in the "moderate" category. The conclusion from the data results is that the average level of anxiety from the two factors, namely the intrinsic factor and the extrinsic factor, is in the "moderate" category. It can be concluded that tennis referees continue to improve cognitive control, especially anxiety. So that anxiety will be more controlled and can lead the match well